Why do team-sport athletes drink fluid in excess when exercising in cool conditions? - Bargh, M. J.; King, R. F. G. J.; Gray, M. P.; Jones, B. (Applied Physiology, Nutrition, and Metabolism, 2017)
This study assessed the potential physiological and perceptual drivers of fluid intake and thirst sensation during intermittent exercise. Ten male rugby players (17 ± 1 years, stature: 179.1 ± 4.2 cm, body mass (BM): 81.9 ± 8.1 kg) participated in six 6-min small-sided games, interspersed with 2 min rest, where fluid intake was ad libitum during rest periods. Pre- and postmeasurements of BM, subjective ratings (thirst, thermal comfort, thermal sensation, mouth dryness), plasma osmolality (POsm), serum sodium concentration (S[Na+]), haematocrit and haemoglobin (to calculate plasma volume change; PV) were taken. Fluid intake was measured during rest periods. BM change was -0.17 ± 0.59% and fluid intake was 0.88 ± 0.38 L. Pre- to post-POsm decreased (-3.1 ± 2.3 mOsm/kg; p = 0.002) and S[Na+] remained similar (-0.3 ± 0.7 mmol/L, p = 0.193). DeltaPV was 5.84 ± 3.65%. Fluid intake displayed a relationship with pre-POsm (r = -0.640, p = 0.046), prethermal comfort (r = 0.651; p = -0.041), DeltaS[Na+] (r = 0.816, p = 0.004), and DeltaPV (r = 0.740; p = 0.014). DeltaThirst sensation displayed a relationship with premouth dryness (r = 0.861, p = 0.006) and ?mouth dryness (r = 0.878, p = 0.004). Yet a weak positive relationship between Deltathirst sensation and fluid intake was observed (r = 0.085, p = 0.841). These data observed in an ambient temperature of 13.6 ± 0.9 °C, suggest team-sport athletes drink in excess of fluid homeostasis requirements and thirst sensation in cool conditions; however, this was not influenced by thermal discomfort.